BERAN CASA 1864–1896 (Heritage, 2025)
After concluding an armistice with Montenegro and the foundation of town of Berane in 1862, Skadar governor separated Donje Vasojevic from Gusinje Nahija into special Beran district. After Montenegrinian – Turkish confining 1858/59 the part of Vasojevic that remained inside the Turkish state is called Donje Vasojevic. They often called this area as Sabanagic nahija, after the name of the richest feudal family from Plav and Gusinje which possesed the most of bey’s and aga’s estate, in the area of Beran nahija and Beran casa. Reformation of Beran casa administration in February 1864 separated it from Skadar sandzak and attached to newly established Novi Pazar sandzak, which was part of Bosnian alayet, in fact from 1865, Bosnian vilayet. By the decision of Berlin contract Beran casa remained inside tht Turkish Empire. Since September 1881 until 1912 Beran casa was inside of newly established  Pec sandzak which belonged to Kosovo vilayet. The most population in Beran hahija were Vasojevic who attached their origin to the founder of a family Vasa and Nemanjic family. The other part of  orthodox population were other clans, brotherhoods and smaller tribes, in fact their parts, either they were natives or immigrants from Brdo, Old Montenegro and Herzegovina. In XIX century there were changes in the structure of population in Beran casa. Political and economic situation had an influence on this, as well as inside the area itself and in their surrounding. Since the Turkish authorities gave some privileges to islam population, in the first half of XIX century there was a huge wave of accepting Islam, as well as Vasojevic and non-Vasojevic brotherhoods. Immigration of Muslim population (muhadziri) from Bosnia and Herzegovina and those parts that belonged to Serbia and Montenegro according to the decision of Berlin Congress, also led to the changes in population structure. Increasing in number of Muslim population, hard agricultural relationships and harder pressure of Turkish authorities have led to new immigrations of Serbs from Beran casa. But that number was not big enough, so thanks to  compactness, better agricultural relationships and strong national-liberation movement Serbs remained the most numerous population in Beran casa. Villages around Berane were inhabited with Serbian population,  and in Berane itself there were more Muslim population.  Beran casa was unique and was not separated in mudirluk and nahija. In Berane there was a mudir (chief to people) and bimbasha (commander, major) with a thousand of people (soldiers and policemen). From the beginning there were two Serbs next to a mudir. Each village elected  prince or peasant, and the mudir confirmed the election. Prince was obliged to be at service for Turkish authorities. Because of striving of ordhodox population not do interfere with Turkish authorities, princes in Beran nahija had a great influence in their village and they often refused  to carry out an order from Turkish authorities.Beran casa represented one of the most strategic areas in this period. Turks tended to supervise their control over this teritory and organise their authorities and Austro-Hungary tended to impose their rule over this area and to provide the path to Thessaloniki.Orthodox population were opposed to these plans of Turkey and Austro-Hungary defending their homes, at the same time they fight for economic and national exemption, they wanted to unite and to attach themselves with Gornje Vasojevic and to one of the free Serbian States.
Keywords: Berane, casa, sandzak, Serbia, Montenegro, Donji Vasojevic, Gornje Polimlje, Berlin Congress, Serbian population, peasant.